Pre-exercise Carbohydrate Drink Adding Protein Improves Post-exercise Fatigue Recovery - Tan, Albert Yi-Wey; Hamzah, Sareena-Hanim; Huang, Chih-Yang; Kuo, Chia-Hua (Frontiers in Physiology, 2021)
Purpose: To assess the requirement of protein in pre-exercise carbohydrate drinks for optimal endurance performance at high intensity and post-exercise fatigue recovery. Methods: Endurance performance at 85% V̇O2peak of young men (age 20 ± 0.9 y, V̇O2peak 49.3 ± 0.3 L/min) was measured for two consecutive days by cycling time to exhaustion and total work exerted 2 h after 3 isocaloric supplementations: RICE (50 g, protein: 1.8 g), n = 7; SOY+RICE (50 g, protein: 4.8 g), n = 7; or WHEY+RICE (50 g, protein: 9.2 g), n = 7. Results: Endurance performance was similar for the 3 supplemented conditions. Nevertheless, maximal cycling time and total exerted work from Day 1 to Day 2 were improved in the WHEY+RICE (+21%, p = 0.05) and SOY-RICE (+16%, p = 0.10) supplemented conditions, not the RICE supplemented condition. Increases in plasma IL-6 were observed 1 h after exercise regardless of supplemented conditions. Plasma creatine kinase remained unchanged after exercise for all 3 supplemented conditions. Increases in ferric reducing antioxidant power after exercise were small and similar for the 3 supplemented conditions. Conclusion: Adding protein into carbohydrate drinks provides no immediate benefit in endurance performance and antioxidant capacity yet enhances fatigue recovery for the next day. Soy-containing carbohydrate drink, despite 50% less protein content, shows similar fatigue recovery efficacy to the whey protein-containing carbohydrate drink. These results suggest an importance of dietary nitrogen source in fatigue recovery after exercise.